Chronology and late-Holocene evolution of Caleta de los Loros, NE Patagonia, Argentina. (August 2018) - Sander, Lasse; Pejrup, Morten; Murray, Andrew Sean; Perillo, Gerardo ME; Raniolo, Luís Ariél; Fruergaard, Mikkel
Geomorphological and sedimentary records of Holocene coastal deposits may serve as archives for the local reconstruction of trends in coastal evolution and of the key forcing parameters controlling long-term change. We here present new observations on the sedimentology, chronology, and surface properties of a coupled beach ridge and coastal lagoon system located on the northern shore of San Matías Gulf, NE Patagonia, Argentina. The study is based on remotely sensed data, sediment cores, and a large number of samples dated using optically stimulated luminescence (OSL). The field site is located in a topographical depression within a cliffed shoreline composed of friable sand and gravel stones. The oldest preserved lagoonal deposits formed in the protected inner part of the system c. 2300 years ago. An up to 4-km-wide strandplain prograded rapidly between c. 1000 and 500 years in the more exposed western part of the system. Lagoonal deposition occurred primarily during the last 500 years. The chronology and spatial arrangement of landforms appear to result from a switch-over in sediment delivery probably caused by local implications of major shifts in climate regime. Even though we were not able to identify or benchmark the precise triggers of geomorphological change at Caleta de los Loros, our study presents an example of the potential importance of environmental changes on the rapid and non-linear development of coastal sedimentary systems.